ARE INTRAVITREAL INJECTIONS WITH ULTRATHIN 33-G NEEDLES LESS PAINFUL THAN THE COMMONLY USED 30-G NEEDLES?. Issue 9 (September 2015) - van Asten, Freekje; van Middendorp, Henriët; Verkerk, Samuël; Breukink, Myrte B.; Lomme, Roger M. L. M.; Hoyng, Carel B.; Evers, Andrea W.; Klevering, B. Jeroen
Abstract : Purpose: This study investigated whether pain from intravitreal injections (IVIs) can be reduced by injecting with a 33-G needle instead of the commonly used 30-G needle. Additionally, several pain-related psychological factors were explored as predictors of outcome. Methods: This randomized crossover trial included 36 patients who received injections with both needles in randomized order. After the injection, patients rated IVI pain on a 0 to 10 scale. Before injection, distress and pain expectations were assessed. Afterward, patients rated the IVI procedure and anticipated consequences. In addition, we assessed the force necessary to penetrate the sclera for both needles in porcine eyes. Results: The 33-G needle did not result in lower IVI pain (2.8 vs. 3.1, P = 0.758) but tended to cause less vitreal reflux (0 vs. 5 times, P = 0.054). Factors related to more pain were distress, expecting IVI pain and discomfort, dissatisfaction with the preparation procedure, anticipating negative consequences, and female gender. Patients regarded povidone–iodine disinfection as particularly unpleasant. Exploration of the needles' mechanical properties showed that 33-G needles penetrate the sclera more easily. Conclusion: The thinner 33-G needle does not reduce IVI pain but may limit scleral damage. Future efforts could be aimed at optimizing patient information, reducing distress, and the use of better tolerable disinfectants. Abstract : This randomized crossover trial showed that pain from intravitreal injections could not be reduced by injecting with an ultrathin 33-G needle instead of the commonly used 30-G needle but tended to cause less vitreal reflux. Exploration of pain-related factors indicated that negative expectations and distress contributed to higher pain perception.